Represent the following expressions as a power of the number a (a≠0)
(a⁻¹·a⁻²)⁻³
BRAINLIEST IF YOU ARE THE FASTEST AND HAVE THE Right ANSWER
GO GO GO

Respuesta :

Answer:

  • [tex]a^9[/tex]

Step-by-step explanation:

  • [tex](a^{-1}a^{-2})^{-3}=[/tex]
  • [tex](a^{-1-2})^{-3}=[/tex]
  • [tex](a^{-3})^{-3}=[/tex]
  • [tex]a^{(-3)(-3)}=[/tex]
  • [tex]a^9[/tex]

[tex]\\ \rm\leadsto (a^{-1}a^{-2})^{-3}[/tex]

[tex]\\ \rm\leadsto (a^{-1-2})^{-3}[/tex]

[tex]\\ \rm\leadsto (a^{-3})^{-3}[/tex]

[tex]\\ \rm\leadsto a^9[/tex]

ACCESS MORE